2011
DOI: 10.1136/heartjnl-2011-300792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of subclinical rheumatic heart disease in India: The RHEUMATIC (Rheumatic Heart Echo Utilisation and Monitoring Actuarial Trends in Indian Children) study

Abstract: The prevalence of RHD is several fold higher using echocardiographic screening compared with clinical examination. The prevalence is higher among girls and children of lower socioeconomic status. In the majority of cases, subclinical RHD appears to be non-progressive on medium term follow up. Routine echocardiographic screening may be indicated in populations at high risk of RHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 16 publications
9
127
4
1
Order By: Relevance
“…The prevalence of RHD varies across the globe, the highest being in subSaharan Africa (5.7e55.4/1000 6 ) with least being in the developed nations where the prevalence is less than 1/1000. In India the prevalence of RHD as reported (Table 4) by ICMR, 9,10 Padmavathi, 11 Grover et al, 10 Avasthi et al, 12 Patel et al, 13 Jacob Jose et al 2 Periwal et al, 14 Bhaya et al 4 and Saxena et al 5 varied from 1 to 51/1000. Jacob Jose from Vellore, 2 South India screened 2, 29 829 school children aged 6e18 years.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of RHD varies across the globe, the highest being in subSaharan Africa (5.7e55.4/1000 6 ) with least being in the developed nations where the prevalence is less than 1/1000. In India the prevalence of RHD as reported (Table 4) by ICMR, 9,10 Padmavathi, 11 Grover et al, 10 Avasthi et al, 12 Patel et al, 13 Jacob Jose et al 2 Periwal et al, 14 Bhaya et al 4 and Saxena et al 5 varied from 1 to 51/1000. Jacob Jose from Vellore, 2 South India screened 2, 29 829 school children aged 6e18 years.…”
Section: Discussionmentioning
confidence: 97%
“…Various other studies also revealed higher prevalence rates among females. 10,19 The present study also documented clinical complications associated with RHD. Mitral valve disease accounted for 86% of cases, aortic valve involvement was seen in 7% of cases, and both mitral and aortic valve involvement were seen in 7% cases.…”
Section: Discussionmentioning
confidence: 63%
“…4,12 In one study, clinical examination revealed only 0.8 RHD cases/1000 population, whereas echocardiography revealed 20.4 RHD cases/1000 population. 19 The reported differences in the prevalence of RHD might be due to different diagnostic methods adopted in various studies or due to non-uniformity of the populations studied. Unfortunately, there are few comparable studies in India determining the prevalence of RHD in rural communities in the above 15 years age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] With multiple recent international studies in Mexico and Africa using point of care ultrasound to screen patients for cardiac anomalies, there is hope that similar projects can have promising results in rural Panama. [12,13] In this project, a group of fi rst year medical students traveled to Bocas Del Toro, Panama to visualize basic cardiac anatomy on pediatric patients. Combining the explosiveness of ultrasound in medical education and the need for pediatric cardiac screenings in rural settings, our aim was to determine if minimally trained firstyear medical students were able to successfully identify pediatric cardiac anatomy and cardiac pathology in rural Panama.…”
Section: Introductionmentioning
confidence: 99%